Interactive Multimedia with Problem-Based Learning in Mathematics - Harianto, Nur Aliza; I Gde Wawan Sudatha (Journal of Education Technology, 2023)
Considering that mathematics material has an important role in everyday life, learning media in learning requires learning media to present learning material that is abstract to become concrete. Interactive multimedia can increase student learning outcomes in mathematics. Apart from that, the PBL learning model is able to encourage students to learn actively in solving a problem. Therefore this research aims to develop interactive multimedia with problems based on learning in mathematics for class VII students of junior high school. This type of research is development research with the ADDIE model which includes five systematic stages in it. The data collected are quantitative data and qualitative data using 3 data collection methods, namely interviews, questionnaires, objective tests. The stages of the ADDIE model which consists of five stages, namely the stages of analysis, design, development, implementation and evaluation. The results of this study indicate that problem-based interactive multimedia learning is valid with very good qualifications. Moreover multimedia interactive learning with problem-based learning was effectively used in learning class VII mathematics set material at junior high school.